Exploring Relationships and Information Exchange in Grocery Supply Chains: a Case Study of the Enablers and Inhibitors. - Barratt, Mark A. (Cranfield University, 2002)
The last decade has seen a growing interest from academics and practitioners in the development of collaborative supply chain relationships based on information exchange. Most of the evidence gathered within this management research area has been biased towards the role of the buyer/supplier dyadic exchange in the integration of the supply chain. The role of the other parties and the systemic nature of supply chain management have been relatively ignored. Previous research in this area has also been biased due to the narrow focus of investigation, with one problem being obtaining access to all parties involved in the supply chain. The purpose of this study was to overcome the aforementioned research biases and therefore, contribute to the understanding of the collaborative relationship development process from a broader supply chain perspective. Open access was gained to six organisations across three tiers of a coffee supply chain in the UK grocery sector. Within this context, a theory building approach was applied to the data collected in the case study. Through constant comparison and coding of data from multiple strategic, tactical, operational, inter- and intra-organisational exchanges within the same context, several findings were made. An interesting finding from the research is the evolving role of the supply chain integrator, whereby the manufacturer seeks to balance the needs of its retail customers with the sourcing and procurement of raw and packaging materials from its suppliers. In terms of the concepts of supply chain relationships and information exchange, there are a number of common enablers and inhibitors. The inter-relationship between the two concepts is however complex and requires further study. The other findings of the research are expressed as a tentative theoretical framework and a series of new emerging enablers and inhibitors to collaborative relationships and information exchange in the supply chain. Finally the enablers and inhibitors grounded from the case study provide a guide to the relational and often context specific factors that can influence the development of collaborative supply chain relationships based on information exchange.